2013
DOI: 10.1158/2159-8290.cd-12-0231
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic and Wild-type Ras Play Divergent Roles in the Regulation of Mitogen-Activated Protein Kinase Signaling

Abstract: H-Ras, K-Ras, and N-Ras regulate cellular growth and survival and are often activated by somatic mutation in human tumors. Although oncogenic lesions occur in a single Ras isoform within individual tumors, it is unclear whether the remaining wild-type isoforms play supporting roles in tumor growth. Here, we show that oncogenic and wild-type Ras isoforms play independent and nonredundant roles within the cell. Oncogenic Ras regulates basal effector pathway signaling, whereas wild-type Ras mediates signaling dow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
171
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(186 citation statements)
references
References 49 publications
15
171
0
Order By: Relevance
“…Further, cooperative loss of these feedback mechanisms was shown to promote Ras-induced leukemogenesis (50). EphA2 has been suggested to be one such negative feedback regulator inhibiting KRAS downstream signaling pathways (30,55). Our results show that loss of EphA2 promotes cell proliferation by activating proliferative signaling and transcription programs.…”
Section: Discussionmentioning
confidence: 53%
“…Further, cooperative loss of these feedback mechanisms was shown to promote Ras-induced leukemogenesis (50). EphA2 has been suggested to be one such negative feedback regulator inhibiting KRAS downstream signaling pathways (30,55). Our results show that loss of EphA2 promotes cell proliferation by activating proliferative signaling and transcription programs.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, even a high expression of wild type KRAS protein is not itself able to induce metabolic reprogramming. This observation is interesting in light of recent work by Young et al, who demonstrated that both the mutant and wild type KRAS alleles play distinct roles in regulating signaling through the epidermal growth factor pathway (61).…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies demonstrated that wild-type Ras proteins contribute to tumorigenesis in Ras-mutant cancer cells (21)(22)(23)(24). However, the oncogenic roles of Ras in Ras wild-type cancers have yet to be established.…”
Section: Discussionmentioning
confidence: 99%